Ligand-capped pristine and doped ZnO2 nanoparticles for enhanced photocatalytic methylene blue degradation: A DFT-supported study - ULLAH, IMRAN; Neder, Reinhard; Irfan Khan, Muhammad; Din, Inam Ud; Parwaz, Huma; Sufian, Suriati (Ceramics International, 2025)
In the present work, ligand-assisted zinc peroxide (ZnO2) nanoparticles (NPs) and doped ZnO2 NPs (manganese (Mn) and cobalt (Co)) were synthesized via the co-precipitation method and characterized through complementary techniques. Organic ligands, including citrate (cit), 1,5-diphenyl-1,3,5-pentanetrione (pent), and dimethyl-L-tartrate (dmlt), were used to stabilize the NPs and tune their bandgap through Mn and Co doping, thereby enhancing the photocatalytic degradation of methylene blue (MB) dye. The XRD data refinement revealed cuboctahedral-shape crystallites/NPs with diameters ranging from 3 to 12.7 nm. Tauc's relation supported an optical bandgap of 2.96 eV upon 3 % Mn incorporation, which is lower than 3.07 eV for pristine ZnO2 (cit-capped) NPs. In 150 min, cit-capped pristine ZnO2 NPs degraded 63.34 % of MB dye; this rate increased to 77.94 %, 93 % upon 3 %, 5 % Mn-doping, and 85.13 %, 81.24 % upon 3 %, 5 % Co doping, respectively. A similar trend was observed for dmlt-capped NPs; pristine ZnO2 NPs degraded 63.72 % of dye and reached to 72.26 %, 74.25 % upon 3 %, 5 % Mn-doping, and 78.56 %, 79.71 % upon 3 %, 5 % Co-doping in 150 min, respectively. Notably, pent-capped ZnO2 NPs degraded 98.89 % in 90 min. However, the performance was adversely affected by Mn and Co-doping (83.20 %, 97.35 % for 3 %, 5 % Mn-doped and 78.65, 73.68 % for 3 %, 5 % Co-doped). DFT calculations suggest that Mn and Co-incorporation into ZnO2 lattice improved thermodynamic and mechanical stability as well as chemical reactivity. The kinetics analysis showed that all reactions follow the pseudo-first-order kinetic model with R-squared values ranging from 84.0 to 98.5. This work demonstrates how doping can improve the performance of ligand-assisted ZnO2 photocatalysts for enhanced dye degradation.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Co-precipitation; DFT; Doped-Zinc Peroxide; Methylene Blue dye; Photodegradation; Zinc Peroxide